Endostatin-based anti-angiogenic therapy and immune modulation: mechanisms and synergistic potential in cancer treatment - Sun, JingTao; Ren, Simeng; Zhao, QingYun; He, JiaXin; Wang, YaXuan; Ren, MingHua (Frontiers in Immunology, 2025)
Cancer remains a critical global health challenge, driven by tumor angiogenesis and immune evasion. Endostatin, a collagen XVIII-derived fragment, uniquely suppresses angiogenesis and reprograms the immunosuppressive tumor microenvironment (TME), positioning it as a dual-targeting therapeutic. Despite clinical advancements with recombinant human endostatin (rhEs), challenges such as transient efficacy and delivery limitations persist. Emerging strategies integrating nanotechnology, combination therapies, and immunomodulation (e.g., TAM reprogramming, immune checkpoint synergy) aim to amplify its therapeutic potential. This review synthesizes current knowledge on endostatin’s mechanisms in angiogenesis inhibition and immune modulation. It further evaluates its clinical efficacy across solid tumors and explores innovative strategies to overcome translational barriers. By dissecting technological advancements, controversies, and synergistic opportunities with radiotherapy, chemotherapy, and immunotherapy, we aim to chart a roadmap for harnessing endostatin’s full potential in redefining precision cancer therapeutics.